Reproductive Aspects of Scad Fish (Selar crumenophthalmus) Landed at the Fish Landing Base of PPI Tanjung Luar, East Lombok - Suciq Aldauria; Karnan Karnan; M. Yamin; I Wayan Merta (Jurnal Pijar MIPA, 2025)
Selar crumenophthalmus, known as the bigeye scad, is a commercially important small pelagic fish widely exploited in East Lombok waters. This study aims to examine the reproductive characteristics of the species, including gonadal maturity stages (GMS), gonadosomatic index (GSI), sex ratio, length–weight relationship, and length–fecundity relationship, based on samples collected at PPI Tanjung Luar from June to August 2025. This study employed a descriptive exploratory research design, with samples collected using quota sampling consisting of 90 individuals who landed at PPI Tanjung Luar from June to August 2025, and the data were analyzed descriptively. The species designated GMS I–V, with GMS II and III being the most dominant stages across months. The highest GSI values for both sexes occurred in June, indicating the peak spawning period, with female GSI reaching 2.34% and male GSI 0.80%. Monthly sex ratios shifted from 2.13:1 (June) to 0.64:1 (July) and 1:1 (August). The length–weight relationship showed positive allometric growth in males (b = 3.05) and negative allometric growth in females (b = 2.189). Fecundity ranged from 9,312–11,843 eggs in June and 8,495–15,006 eggs in July, with a strong positive correlation to body length in mature females. These findings indicate that reproduction peaks in June, providing essential information for the sustainable management of the species in Tanjung Luar.